The difference of 17% ethylenediaminetetraacetic acid irrigation material contact time of 60 seconds and 30 seconds toward of cleanliness of apical third root canal wall - Wijaya, Yunita; Natasasmita, Setiawan; Sukartini, Endang (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2011)
Root canal preparation is one important step in endodontic treatment, involves the cleaning and the shaping of the root canal debris. Root canal cleaning effectiveness depends on the preparation bio-mechanical and irrigation. Purpose of this study was to evaluate the cleanliness of apical third of root canal wall from of debris, with the contact time of 17% EDTA irrigation material for 60 seconds and 30 seconds after root canal preparation using rotary NiTi instruments. This quasi-experimental study was carried out invitro, with random sampling technique. The sample used was 20 central maxillary incisors that have been extracted and divided into two experimental groups of 10 teeth each. The results were analyzed using student t statistics, showed that the average value of the debris of the two groups differed significantly. The contact time of 60 seconds of 17% EDTA showed cleaner root canal than the 30 seconds. The conclusion of this study was there were the differences of the cleanliness of apical third of the root canal with the 60 seconds contact time of 17% EDTA irrigation materials than 30 seconds contact time.